МЕДИА ТИЛИНДЕ МӘНИ АЛМАСЫӮ ЖАҒДАЙЫ (ПРОЦЕСИ): ТЕОРИЯЛЫҚ АНАЛИЗ - Толеўбаева, А.О. (FAN va JAMIYAT, 2022)
The article examines the growing interest of linguists in the study of the language of the newspaper, the reasons for this, firstly, that the newspaper is the oldest media that embodies the basic stylistic methods and tools of the media language, and secondly, from a linguistic description, newspaper texts convenient for comprehensive study and research. The newspaper can perform not only informational but also pragmatic functions through the use of semantic transfer methods. The features of the metaphor that the newspaper text also serves as an important semantic factor have been explored.